High Hydrostatic Pressure Effect on Chemical Composition, Color, Phenolic Acids and Antioxidant Capacity of Cape Gooseberry Pulp (Physalis Peruviana L.) - Galotto-Lopez, M; Lopez-Polo, J (Academic Press, 2014)
The aim of this study was to evaluate the effects of high hydrostatic pressure (HHP) at 300, 400 and 500 MPa/1, 3 and 5 min on nutritional and antioxidant properties of Cape gooseberry pulp after immediate application and after 60 days of storage. Proximal analysis, color, phenolic acids content and antioxidant capacity were determined. When analyzing the immediate effect of different treatments, a clear influence of HHP was observed in all the components of the proximal analysis. Regarding color, none of the three chromatic parameters showed significant differences with control leading to a minimum ?. E at 300 MPa/3 min. Changes in bound and free phenolic acids were evidenced after treatments. The maximum levels of TPC as well as antioxidant capacity were observed at 500 MPa/5 min. By the end of storage, all treated samples discolored leading to ?. E = 14.9 at 500 MPa/5 min. The profile of free and bound phenolic acids presented differences compared to Day 0. The antioxidant capacity by means of ORAC increased for treatments above 300 MPa/5 min indicating the effectiveness of these treatments for the production of functional products based on gooseberry pulp. For treatments above 400 MPa/3 min, molds and yeasts were not detected. © 2014 Elsevier Ltd.
Keywords: High hydrostatic pressure; Antioxidant capacity; Phenolic compounds; Functional foods; Cape gooseberry